MANAJEMEN PESERTA DIDIK DALAM PERSPEKTIF AL-QURAN DAN HADITS - Nur Hidayatul Hasanah, Siti; Riza Zainuddin, Mohammad (LPPM STAI Muhammadiyah Probolinggo, 2023)
This article aims to discuss Student Management according to the Al-Quran an Hadith. The method used is a literature review, namely a general study of Student Management from various sources and references. The Quran is a guide to human life that regulates life from various aspects ranging from social, economic, worship, education and so on. There are many stories in the Quran about the learning process of provious prophets such as the of story of Propet Musa meeting Prophet Khaidir, the story of Prophet Isa, the story of Prophet Yahya, the story of Propeth Ibrahim and Luqmanul Hakim which are immortalized in the Quran about educate their children to always remember Allah and always remind them not to associate partners with Allah and instruct their children to always do good, uphold the truth and be good students with good morals. Students are an important component in an Islamic education process.